Development of hybrid UHPC-NC beams: A numerical study. (15th April 2021) - Kadhim, Majid M.A.; Jawdhari, Akram; Peiris, Abheetha
Highlights: A hybrid beam is proposed comprising UHPC and NC sections. A 3D FE model is developed to study the hybrid member, showing excellent calibrations with test results. A hybrid beam with UHPC only 50% of total length developed the full capacity of all-UHPC beam. Ductility and failure mode can be improved by using dowel reinforcement, rough surface, or outward inclination for UHPC-NC interface. A theoretical model is also developed and showed good results for most cases. Abstract: The mechanical properties and durability of ultra-high performance concrete (UHPC) are superior to those of normal concrete (NC). However, because UHPC is much more expensive than NC, it must be used strategically to maximize its exceptional compressive strength and sustained post-cracking tensile strength. This study develops a finite element (FE) model that represents the behavior of UHPC beams in flexure. The model is validated using previous experimental research which included UHPC beams, both with and without steel fibers, and four different reinforcement ratios. What distinguishes this study from previous efforts is that it also leverages the validated UHPC FE model to evaluate the feasibility of a hybrid reinforced concrete beam composed of both UHPC and NC. Several methods of using UHPC and fabricating a hybrid beam are studied. For a reinforcement ratio ( ρ ) of 0.009, a hybrid UHPC-NC beam with only the middle 50% composed of UHPC ( Lu /L  = 0.5) achieves the same capacity as a beam made entirely of UHPC when the NC's compressive strength is 30 MPa or more. Using dowel bars at the UHPC-NC interface improves beam ductility and shifts the failure location away from the interface. An outward inclination ( θ ) of 45° at the UHPC-NC interface also improves ductility of the Lu /L  = 0.5 hybrid beam. The novel hybrid UHPC-NC beam developed in this study thus obtains strength and ductility values similar to or better than those documented in beams made completely of UHPC, but at a much lower cost. Predictive equations are proposed to evaluate the ultimate capacity of the hybrid UHPC-NC beam, and the results are compared with FE analysis results.